1959
DOI: 10.1063/1.1735125
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Photovoltaic Effect

Abstract: Vacuum evaporated films of cadium telluride have been prepared that show photovoltages as high as 100 v/cm of film length. An oblique angle of deposition of the vapor onto the substrate is required. The photovoltage saturates at high light intensities and low temperatures. At all other light intensities and temperatures it has the same functional dependence on light intensity as that of ordinary p-n junctions. The short-circuit current varies linearly with light intensity at all temperatures and is only weakly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

1968
1968
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 11 publications
4
29
0
1
Order By: Relevance
“…12 is the value of a photovoltage of 10 V at visible wavelengths (400-780 nm) with a light intensity of 200 mW cm −2 . The observation of very large photovoltages in ferroelectric materials has been known for many decades (Starkiewicz et al, 1946,Goldstein and Pensak, 1959,Grekov et al, 1970,Brody, 1973,Glass et al, 1974. Recent examples of large photovoltages are the measurements of 7 V in 25 μm (Pb,La)(Zr,Ti)O 3 at 1.5 mW cm −2 (Pintilie, 2011), 8.8 V with 4 mW cm -2 UV light on KBiFe 2 O 5 (Zhang et al, 2013,Zhai et al, 2015) and 3.6 V in 50 μm BiFeO 3 , see Fig.…”
Section: Phenomenology Of Ferroelectric Solar Cellsmentioning
confidence: 99%
“…12 is the value of a photovoltage of 10 V at visible wavelengths (400-780 nm) with a light intensity of 200 mW cm −2 . The observation of very large photovoltages in ferroelectric materials has been known for many decades (Starkiewicz et al, 1946,Goldstein and Pensak, 1959,Grekov et al, 1970,Brody, 1973,Glass et al, 1974. Recent examples of large photovoltages are the measurements of 7 V in 25 μm (Pb,La)(Zr,Ti)O 3 at 1.5 mW cm −2 (Pintilie, 2011), 8.8 V with 4 mW cm -2 UV light on KBiFe 2 O 5 (Zhang et al, 2013,Zhai et al, 2015) and 3.6 V in 50 μm BiFeO 3 , see Fig.…”
Section: Phenomenology Of Ferroelectric Solar Cellsmentioning
confidence: 99%
“…-Equation (8) shows that at high tempera tures, the photovoltage should vary with the temperature as the sum of several exponen tial terms; therefore, a semilogarithmic plot of voltage against reciprocal temperature should, in general, be curved. However, it is possible that straight sections will occur in temperature ranges where only one trapping level predominates either because of the depth or the t r a p concentration or both.…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 99%
“…Photovoltages, much larger than the band-gap energy ͑E g ͒ of the semiconductor, have been observed in obliquely deposited thin films of a large number of semiconductors [1][2][3][4][5][6][7][8][9][10][11][12][13][14] on transparent substrates under normal illumination. This effect is commonly known as the anomalous photovoltaic effect ͑APV͒.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies 1-24 of a range of materials have established beyond a doubt that a necessary condition for the appearance of the anomalous photovoltage ͑APV͒ is that the semiconductor material should be evaporated onto a substrate at an angle to the normal leading to skewed columnar growth. 8 However, the precise conditions under which successful APV structures may be obtained are far from clear and it has been difficult to obtain reproducible results. 8 Kallmann et al., 12 during their studies on Ge and Si films of ϳ1 m thickness formed by vacuum evaporation, observed that generally the absolute value of the photovoltage measured between two metal contacts separated by 1 cm was larger at lower temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation